Analysis of the association between socio-demographic variables, juvenile offending, and formal vs. informal juvenile justice system handling in a non-urban sample - Phillippi, Jr (2007)
PURPOSE: This study compares and contrasts first-time juvenile offenders enrolled in a community-based intervention program whose cases were processed either informally or formally, and examines empirically- and conceptually-relevant contributors to re-offending. METHODS: This is a longitudinal, secondary analysis of 1072 male and female offenders. The study includes descriptive univariate analyses; chi-square bivariate analyses of each independent variable with the dependent variables (level of processing and recidivism at both one and three years); and binary logistic regression analyses to identify significant predictors of the dependent variables. Independent variables include age, gender, race, family structure, marital status of biological parents, family income, number of children in the home, type of offense, program completion, and POSIT risk scores (including substance abuse, physical health, mental health, family relationships, peer relationships, educational status, and aggressive behavior/delinquency). RESULTS: Variables significantly associated with level of processing were race, gender, type of offense, marital status of the biological parents, number of children in the home, and family relationship risk. Multivariate predictors of formal levels of processing were age, gender, race, type of offense, marital status of biological parents, and the number of children in the home. For one-year recidivism, analysis showed significant associations with level of processing and educational risk. Recidivism within three years was associated with age, program completion, and educational risk. Logistic Regression models showed family income, marital status of biological parents, and program completion are predictors of one-year recidivism. For predictors of three-year recidivism, age, family income, program completion, marital status of the biological parents, and mental health risk had significant partial effects. CONCLUSION: A greater understanding of the factors that are associated with and predict level of juvenile justice processing and recidivism for first-time juvenile offenders is critical to the success of the juvenile justice system and its associated intervention efforts as this is the group of youth active in the system in the largest proportions at any given time. This study lends to that understanding and offers analysis of both male and female youth in a non-urban setting and examines how family characteristics are associated specifically with level of processing, which are unique attributes compared with juvenile justice studies in the literature